Case Report: Pathogenic PNPLA2 variants and nonsense-mediated mRNA decay result in an early-onset neutral lipid storage disease with myopathy - Missaglia, Sara; Martegani, Eleonora; Angelini, Corrado; Horvath, Rita; Karcagi, Veronika; Pal, Endre; Tavian, Daniela (Frontiers in Genetics, 2025)
Neutral Lipid Storage Disease with Myopathy (NLSDM) is a rare lipid metabolism disorder caused by impaired Adipose Triglyceride Lipase (ATGL) activity, leading to neutral lipid accumulation in various tissues. It typically manifests with progressive skeletal myopathy, with an onset of around 35 years. In addition, some patients develop cardiomyopathy and liver dysfunction. Herein, we report the molecular characterization of a 27-year-old Hungarian patient and his family in whom two severe PNPLA2 mutations led to complete loss of ATGL production in the patient’s tissues. DNA sequencing revealed a nonsense (c.24G>A) and a frameshift mutation (c.798dupC) in the PNPLA2 gene. RNA analysis showed nonsense-mediated decay of the c.798dupC transcript, while c.24G>A was normally expressed in the patient. However, Western blot analysis did not detect ATGL protein production. From a clinical perspective, our patient exhibited pes planus, proximal muscle weakness of the lower limbs and elevated CK levels from the age of six. MRI and biopsy revealed lipid accumulation, and leukocytes showed Jordans’ anomaly. The muscle weakness progressed, and cardiomyopathy and hepatic steatosis were also observed recently. The case highlights two severe PNPLA2 mutations leading to complete ATGL deficiency and an unusual early-onset myopathy in childhood.